Fundamentos jurídicos en contra de la incorporación de nuevos elementos de convicción en audiencia de prisión preventiva - Prieto Durand, Dayana Karolina (2024)
"In the investigation that was carried out, an analysis was made of the procedural legal institution, which covered preventive detention quite a bit, but referred to an issue strictly related to the process of the hearing where its imposition is discussed, and, specifically, the possibility or not that new or additional elements of conviction can be incorporated to support their claim of foundation of the measure of personal coercion; In this context, the following was proposed as a problem statement: “What are the legal bases that prevent the incorporation of new elements of conviction in the preventive detention hearing in the Peruvian criminal process?” In relation to the problem posed, the following general objective was set: ""Determine what are the legal bases that prevent the incorporation of new elements of conviction in the preventive detention hearing in the Peruvian criminal process"", based on this objective, it was made a development of the main theoretical bases to cement the topic, and then used the doctrinal, jurisprudential and analysis methods of article 268 (hermeneutical method), as well as comparative law, to carry out the respective analysis of the results, using the techniques of recording and documentary analysis, which then led me to positively test the hypothesis and outline the respective conclusions. Finally, use was made of everything discussed as support or legal foundations, so that in the end, a change of lege ferenda is proposed, so that normatively, it is expressly established that it is not possible to incorporate elements of additional convictions, but those that support the investigation must be those elements that make up the preventive detention requirement formulated by the prosecution"